Enjoyment and Information Gain in Science Articles; A Way to Reach Minorities: Multicultural Awareness; A Longitudinal Task of the Selective Exposure Hypothesis; Dakota Farmers and Ranchers Evaluate Crop and Livestock Surveys - Larry Meiller; John Fett (Journal of Applied Communications, 1980)
Reviews of "Enjoyment and Information Gain in Science Articles," by Alan Hunsaker; "A Way to Reach Minorities: Multicultural Awareness," by Benjamin Yep and Marynell Hollenbeck; "A Longitudinal Task of the Selective Exposure Hypothesis," by Michael A. Milburn; and Dakota Farmers and Ranchers Evaluate Crop and Livestock Surveys, by Calvin Jones, Paul Sheatsley and Arthur Stinchcombe.